CONSUMER PERCEPTIONS OF SAJIKU BRAND SEASONING FLOUR, AJINOMOTO PRODUCTS AT A GENERAL STORE (CASE STUDY AT NISA SHOP) - susilowati, susilowati; Ruliaty, Ruliaty; Indrayani, Syarthini (Perpustakaan dan Penerbitan Unismuh Makassar, 2019)
This study aims to determine perceptions of flour spices brand Sajiku at grocery store ( case study at Nisa store ) .Type of research used in research is case study research with qualitative descriptive approach. Data obtained through questionnaires, interviews, observations and documentation. Samples in this study were obtained by accidental sampling technique that is 30 people. Data obtained from respondents tabulated then analyzed with Likert Scale. Based on the result of research from the questionnaire filling by respondents it can be concluded that the majority of respondents gave answers category Strongly Agree about Sajiku spice flour. This proves that Sajiku brand seasoning flour is well received by consumers.